ANALISIS PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP CITRA MEREK DAN KEPUTUSAN PEMBELIAN PRODUK SEPATU BATA DI KOTA SEMARANG - Rosady, Ria Safitri; Kusumawardhani, Amie (Faculty of Economics and Business Diponegoro University, 2018)
PT Sepatu Bata Tbk has decreased sales which can affect the brand image of company. Brand image is one of the factors that form the brand equity and can give a description of consumer perceptions of a brand. Every company is required to conduct marketing activities whose main purpose is to influence consumer perception on brand, build brand image in the mind of consumer so that later will have an impact on sales increase, and can maximize market share in accordance with company expectation.The purpose of this study to analyze product quality and promotion on brand image and the impact on purchase decision. The population of the study was all consumers who had ever done purchase transaction on bata shoes product, where respondents are Semarang people. The samples in this study were 130 respondents. The method of collecting data through questionnaires. This study uses analytical techniques of Structural Equation Modeling (SEM) with AMOS 22.0 as the analysis instrument.The result show that the product quality has a positive and significant effect on brand image, promotion has a positive and significant effect on brand image, brand image has a positive and significant effect on purchase decision, product quality has not a positive impact on purchase decision, and promotion has a positive and significant effect on purchase decisio.